(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdUdMs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdUdM hgh YbO TQY dbWY GdJLGPH, Cbhd(B: (3CeG KHhJ eTQhYjI GdUdM aj GdLedI agh MJeG dG CTcGd ajg hGdOdjd Ydjg EfeG ghdGA GdcJGH hGdSfI hGLJeGY GdCeIs
(3BNQgG (B:s
(3BNQgG(B: (3hdh cGf UGMH GdHGH (B.. (3ajgG HGdScfi hfMhgG aGdbhd bhdg (B.. (3ceG gh GdeMcj Yf cKjQ (B.. (3Hd QHeG fSH Pdc Zdjge hjOd Ydjg Cfg jchf gh UGMH GdjO Ohf ZjQg ceG gh hGVM(B. (3hGddg hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis